Preparation method of high-toughness lubricating coating on surface of air bearing

By depositing ZnO and MoS2 coatings on the surface of the ball bearing using plasma cleaning and atomic layer deposition technology, and injecting Ag ions, the problem of poor anti-friction and wear performance of the ball bearing in a vacuum environment is solved, and high-strength lubrication performance and long-lasting performance are achieved. Long-lasting coating effect.

CN119332229APending Publication Date: 2025-01-21HYCESS (GUAN) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411497661.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing ball bearings have poor anti-friction and wear performance under vacuum environment, resulting in short service life and prone to jamming failures, increasing the maintenance cost of CT equipment.

Method used

A method for preparing a high-strength lubricating coating on the air bearing surface is adopted, including plasma cleaning to remove surface dirt and oxide layers, depositing ZnO and MoS2 coatings through atomic layer deposition technology, and injecting Ag ions through plasma immersion to improve the film The bonding strength, lubrication properties and electrical conductivity of the layers.

Benefits of technology

It significantly improves the abrasion resistance and service life of the roller bearing, reduce the friction coefficient, prevent the emergence of discharge phenomena, and improve the accuracy and reliability of the bearings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332229A_ABST
    Figure CN119332229A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-toughness lubricating coating on the surface of an air bearing. The preparation method comprises the following steps: S1, carrying out surface cleaning on a ball by adopting an anode layer gas ion source; s2, depositing a ZnO coating by adopting an atomic layer deposition technology; s3, depositing a MoS2 coating by adopting an atomic layer deposition technology; and S4, Ag ions are injected through plasma immersion. According to the preparation method of the high-toughness lubricating coating on the surface of the air bearing, dirt and an oxide layer on the surface of a rolling ball are removed through plasma cleaning, so that the binding force of a film layer is improved, the lubricating performance is further improved, meanwhile, the conductivity of the film layer can be improved, and the discharge phenomenon is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating coatings, and in particular relates to a method for preparing a high-strength and tough lubricating coating on the surface of an air bearing. Background Art

[0002] The CT tube is the core component of the CT machine and is also a high-value consumable. The CT tube usually uses ball bearings. The balls are usually made of steel. The material has low hardness and poor wear resistance. It wears severely in the working environment and is prone to jamming and other failures, causing the hospital to shut down for maintenance. In addition, the lifespan is generally short, and the tube needs to be replaced many times during the life cycle of the CT equipment, which increases costs.

[0003] At present, the main coating preparation technologies include physical vapor deposition and chemical vapor deposition. Chemical vapor deposition technology is used to prepare Pb coatings, or physical vapor deposition technology is used to deposit Ag coatings, but Pb coatings have serious environmental problems. Physical vapor deposition technologies, such as multi-arc ion plating and magnetron sputtering, have poor plasma diffraction capabilities and it is difficult to obtain highly uniform coatings on the surface of the ball. However, atomic layer deposition technology, due to its reliance on gas adsorption reactions, can achieve highly consistent coatings on non-planar and obstructed surfaces.

[0004] Therefore, in order to increase the service life of ball bearings, it is urgently necessary to provide a method for preparing a high-strength and tough lubricating coating on the surface of air bearings to improve the anti-friction and wear performance of the ball in a vacuum environment. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a high-strength and tough lubricating coating on the surface of an air bearing. The surface dirt and oxide layer are removed by plasma cleaning on the surface of the ball to improve the bonding strength of the film layer. While further improving the lubrication performance, the conductivity of the film layer can be improved to prevent the occurrence of discharge.

[0006] To achieve the above object, the present invention provides a method for preparing a high-toughness lubricating coating on the surface of an air bearing, comprising the following steps: S1, using the anode layer gas ion source to clean the surface of the ball; S2, depositing ZnO coating using atomic layer deposition technology; S3, depositing MoS2 coating using atomic layer deposition technology; S4. Plasma immersion implantation of Ag ions.

[0007] Preferably, in step S1, the gas ion source is a mixed gas of Ar and H2; The Ar flow rate is 50sccm-120sccm, the H2 flow rate is 10sccm-30sccm, the bias voltage is -50V--300V, the power is 1kW-5kW, and the time is 30min-90min.

[0008] Preferably, in step S2, the precursor is diethyl zinc, the purity of diethyl zinc is greater than 99.99%, and the carrier gas is high-purity nitrogen, the purity of high-purity nitrogen is greater than 99.999%; The flow rate of diethyl zinc is 100 sccm-200 sccm, and the flow rate of high-purity nitrogen is 100 sccm-200 sccm.

[0009] Preferably, an atomic layer deposition cycle includes diethyl zinc and high-purity nitrogen: 0.05s-0.15s, high-purity nitrogen: 2s-4s, H2O and high-purity nitrogen: 0.05s-0.15s, high-purity nitrogen: 3s-5s; the chamber temperature is 100°C-350°C, and the number of cycles is 100-500.

[0010] Preferably, in step S3, the precursors are MoCl5 and H2S, MoCl5 is heated to 200°C; the carrier gas is high-purity nitrogen, and the purity of the high-purity nitrogen is >99.999%; the flow rate of the high-purity nitrogen is 20sccm-70sccm, and the flow rates of H2S and high-purity nitrogen are 150sccm-250sccm.

[0011] Preferably, an atomic layer deposition cycle includes, MoCl5 and high-purity nitrogen: 0.5s-1.5s, high-purity nitrogen: 15s-25s, H2S and high-purity nitrogen: 0.3s-0.5s, high-purity nitrogen: 15s-25s; the chamber temperature is 420℃-500℃, and the number of cycles is 75-150.

[0012] Preferably, in step S4, the injection voltage is -8 kV to 12 kV, and the plasma density is 1.0×10 8 cm -3 —1.0×10 10 cm -3 , pulse width is 1.0-15μs.

[0013] The present invention adopts the above-mentioned method for preparing a high-toughness lubricating coating on the surface of an air bearing, and the beneficial effects are as follows: (1) The present invention uses atomic layer deposition (ALD) technology to deposit a ZnO layer with good toughness and low toughness on the surface of the ball, thereby improving the plastic deformation ability and thus improving its wear resistance; (2) The present invention uses atomic layer deposition technology to deposit a MoS2 layer in another chamber to improve the lubrication performance of the ball and reduce the friction coefficient; (3) The present invention adopts plasma immersion technology to inject Ag ions, which further improves the lubrication performance while increasing the conductivity of the film layer and preventing the occurrence of discharge phenomena; (4) The coating structure and deposition method can prepare a coating with high lubricity and wear resistance, and obtain high consistency in film thickness, thereby improving the service life and accuracy of the bearing.

[0014] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The present invention is a flow chart of an embodiment of a method for preparing a high-toughness lubricating coating on the surface of an air bearing. DETAILED DESCRIPTION

[0016] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0017] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0018] like Figure 1 As shown, a method for preparing a high-toughness lubricating coating on the surface of an air bearing comprises the following steps: S1. Use the anode layer gas ion source to clean the surface of the ball.

[0019] The gas ion source is a mixed gas of Ar and H2. The Ar flow rate is 50sccm-120sccm, the H2 flow rate is 10sccm-30sccm, the bias voltage is -50V--300V, the power is 1kW-5kW, and the time is 30min-90min.

[0020] S2. Atomic layer deposition technology is used to deposit the ZnO coating. Atomic layer deposition (ALD) technology is used to deposit a ZnO layer with good toughness and low toughness on the surface of the ball to improve the plastic deformation ability and reduce wear.

[0021] The precursor is diethyl zinc, the purity of which is >99.99%, and the carrier gas is high-purity nitrogen, the purity of which is >99.999%.

[0022] The flow rate of diethyl zinc is 100 sccm-200 sccm, and the flow rate of high-purity nitrogen is 100 sccm-200 sccm.

[0023] An atomic layer deposition cycle includes: diethyl zinc and high-purity nitrogen: 0.05s-0.15s, high-purity nitrogen: 2s-4s, H2O and high-purity nitrogen: 0.05s-0.15s, high-purity nitrogen: 3s-5s. The chamber temperature is 100℃-350℃, and the number of cycles is 100-500.

[0024] S3. In another chamber, an atomic layer deposition technique is used to deposit a MoS2 coating to improve the lubrication performance of the ball and reduce the friction coefficient.

[0025] The precursors are MoCl5 and H2S, and MoCl5 is heated to 200°C. The carrier gas is high-purity nitrogen, and the purity of high-purity nitrogen is greater than 99.999%. The flow rate of high-purity nitrogen is 20sccm-70sccm, and the flow rate of H2S and high-purity nitrogen is 150sccm-250sccm.

[0026] An atomic layer deposition cycle includes: MoCl5 and high-purity nitrogen: 0.5s-1.5s, high-purity nitrogen: 15s-25s, H2S and high-purity nitrogen: 0.3s-0.5s, high-purity nitrogen: 15s-25s. The chamber temperature is 420℃-500℃, and the number of cycles is 75-150.

[0027] S4. Plasma immersion implantation of Ag ions.

[0028] The injection voltage is -8kV-12kV, and the plasma density is 1.0×10 8 cm -3 —1.0×10 10 cm -3 , pulse width is 1.0-15μs.

[0029] Embodiment 1 A method for preparing a high-toughness lubricating coating on the surface of an air bearing comprises the following steps: S1. Use the anode layer gas ion source to clean the surface of the ball.

[0030] The gas ion source is a mixed gas of Ar and H2, with an Ar flow rate of 100 sccm, a H2 flow rate of 20 sccm, a bias voltage of -150 V, a power of 3 kW, and a time of 60 min.

[0031] S2. Deposit the ZnO coating using atomic layer deposition technology.

[0032] The precursor is diethyl zinc, the purity of which is >99.99%, and the carrier gas is high-purity nitrogen, the purity of which is >99.999%.

[0033] The flow rate of diethyl zinc is 150 sccm, and the flow rate of high-purity nitrogen is 150 sccm.

[0034] One atomic layer deposition cycle includes: diethyl zinc and high purity nitrogen: 0.1s, high purity nitrogen: 3s, H2O and high purity nitrogen: 0.1s, high purity nitrogen: 4s. The chamber temperature is 200℃, and the number of cycles is 200.

[0035] S3. Depositing a MoS2 coating in another chamber using atomic layer deposition technology.

[0036] The precursors are MoCl5 and H2S, and MoCl5 is heated to 200°C. The carrier gas is high-purity nitrogen, and the purity of high-purity nitrogen is greater than 99.999%. The flow rate of high-purity nitrogen is 50sccm, and the flow rates of H2S and high-purity nitrogen are 200sccm.

[0037] One atomic layer deposition cycle includes MoCl5 and high-purity nitrogen: 1s, high-purity nitrogen: 20s, H2S and high-purity nitrogen: 0.4s, high-purity nitrogen: 20s. The chamber temperature is 450℃ and the number of cycles is 100.

[0038] S4. Plasma immersion implantation of Ag ions.

[0039] The injection voltage was -10 kV and the plasma density was 1.0 × 10 9 cm -3 , the pulse width is 5μs.

[0040] Embodiment 2 A method for preparing a high-toughness lubricating coating on the surface of an air bearing comprises the following steps: S1. Use the anode layer gas ion source to clean the surface of the ball.

[0041] The gas ion source is a mixed gas of Ar and H2, with an Ar flow rate of 100 sccm, a H2 flow rate of 20 sccm, a bias voltage of -150 V, a power of 3 kW, and a time of 60 min.

[0042] S2. Deposit the ZnO coating using atomic layer deposition technology.

[0043] The precursor is diethyl zinc, the purity of which is >99.99%, and the carrier gas is high-purity nitrogen, the purity of which is >99.999%.

[0044] The flow rate of diethyl zinc is 150 sccm, and the flow rate of high-purity nitrogen is 150 sccm.

[0045] One atomic layer deposition cycle includes: diethyl zinc and high purity nitrogen: 0.1s, high purity nitrogen: 3s, H2O and high purity nitrogen: 0.1s, high purity nitrogen: 4s. The chamber temperature is 200℃, and the number of cycles is 200.

[0046] S3. Depositing a MoS2 coating in another chamber using atomic layer deposition technology.

[0047] The precursors are MoCl5 and H2S, and MoCl5 is heated to 200°C. The carrier gas is high-purity nitrogen, and the purity of high-purity nitrogen is greater than 99.999%. The flow rate of high-purity nitrogen is 50sccm, and the flow rates of H2S and high-purity nitrogen are 200sccm.

[0048] One atomic layer deposition cycle includes MoCl5 and high-purity nitrogen: 0.5s, high-purity nitrogen: 20s, H2S and high-purity nitrogen: 0.4s, high-purity nitrogen: 20s. The chamber temperature is 450℃ and the number of cycles is 100.

[0049] S4. Plasma immersion implantation of Ag ions.

[0050] The injection voltage was -10 kV and the plasma density was 1.0 × 10 9 cm -3 , the pulse width is 5μs.

[0051] Embodiment 3 A method for preparing a high-toughness lubricating coating on the surface of an air bearing comprises the following steps: S1. Use the anode layer gas ion source to clean the surface of the ball.

[0052] The gas ion source is a mixed gas of Ar and H2, with an Ar flow rate of 100 sccm, a H2 flow rate of 20 sccm, a bias voltage of -150 V, a power of 3 kW, and a time of 60 min.

[0053] S2. Deposit the ZnO coating using atomic layer deposition technology.

[0054] The precursor is diethyl zinc, the purity of which is >99.99%, and the carrier gas is high-purity nitrogen, the purity of which is >99.999%.

[0055] The flow rate of diethyl zinc is 150 sccm, and the flow rate of high-purity nitrogen is 150 sccm.

[0056] One atomic layer deposition cycle includes: diethyl zinc and high purity nitrogen: 0.1s, high purity nitrogen: 3s, H2O and high purity nitrogen: 0.1s, high purity nitrogen: 4s. The chamber temperature is 200℃, and the number of cycles is 100.

[0057] S3. Depositing a MoS2 coating in another chamber using atomic layer deposition technology.

[0058] The precursors are MoCl5 and H2S, and MoCl5 is heated to 200°C. The carrier gas is high-purity nitrogen, and the purity of high-purity nitrogen is greater than 99.999%. The flow rate of high-purity nitrogen is 50sccm, and the flow rates of H2S and high-purity nitrogen are 200sccm.

[0059] One atomic layer deposition cycle includes MoCl5 and high-purity nitrogen: 0.5s, high-purity nitrogen: 20s, H2S and high-purity nitrogen: 0.4s, high-purity nitrogen: 20s. The chamber temperature is 450℃ and the number of cycles is 100.

[0060] S4. Plasma immersion implantation of Ag ions.

[0061] The injection voltage was -10 kV and the plasma density was 1.0 × 10 9 cm -3 , the pulse width is 5μs.

[0062] Embodiment 4 A method for preparing a high-toughness lubricating coating on the surface of an air bearing comprises the following steps: S1. Use the anode layer gas ion source to clean the surface of the ball.

[0063] The gas ion source is a mixed gas of Ar and H2, with an Ar flow rate of 100 sccm, a H2 flow rate of 20 sccm, a bias voltage of -150 V, a power of 3 kW, and a time of 60 min.

[0064] S2. Deposit the ZnO coating using atomic layer deposition technology.

[0065] The precursor is diethyl zinc, the purity of which is >99.99%, and the carrier gas is high-purity nitrogen, the purity of which is >99.999%.

[0066] The flow rate of diethyl zinc is 150 sccm, and the flow rate of high-purity nitrogen is 150 sccm.

[0067] One atomic layer deposition cycle includes: diethyl zinc and high purity nitrogen: 0.1s, high purity nitrogen: 3s, H2O and high purity nitrogen: 0.1s, high purity nitrogen: 4s. The chamber temperature is 200℃, and the number of cycles is 200.

[0068] S3. Depositing a MoS2 coating in another chamber using atomic layer deposition technology.

[0069] The precursors are MoCl5 and H2S, and MoCl5 is heated to 200°C. The carrier gas is high-purity nitrogen, and the purity of high-purity nitrogen is greater than 99.999%. The flow rate of high-purity nitrogen is 50sccm, and the flow rates of H2S and high-purity nitrogen are 200sccm.

[0070] One atomic layer deposition cycle includes MoCl5 and high-purity nitrogen: 0.5s, high-purity nitrogen: 20s, H2S and high-purity nitrogen: 0.4s, high-purity nitrogen: 20s. The chamber temperature is 450℃ and the number of cycles is 50.

[0071] S4. Plasma immersion implantation of Ag ions.

[0072] The injection voltage was -10 kV and the plasma density was 1.0 × 10 9 cm -3 , the pulse width is 5μs.

[0073] Comparative Example 1 A method for preparing a surface coating of an air bearing comprises the following steps: S1. Atomic layer deposition technology is used to deposit ZnO coating. The precursor is diethyl zinc, the purity of diethyl zinc is greater than 99.99%, and the carrier gas is high-purity nitrogen, the purity of high-purity nitrogen is greater than 99.999%.

[0074] The flow rate of diethyl zinc is 150 sccm, and the flow rate of high-purity nitrogen is 150 sccm.

[0075] One atomic layer deposition cycle includes: diethyl zinc and high purity nitrogen: 0.1s, high purity nitrogen: 3s, H2O and high purity nitrogen: 0.1s, high purity nitrogen: 4s. The chamber temperature is 200℃, and the number of cycles is 100.

[0076] S2. Deposit a MoS2 coating in another chamber using atomic layer deposition technology.

[0077] The precursors are MoCl5 and H2S, and MoCl5 is heated to 200°C. The carrier gas is high-purity nitrogen, and the purity of high-purity nitrogen is greater than 99.999%. The flow rate of high-purity nitrogen is 50sccm, and the flow rates of H2S and high-purity nitrogen are 200sccm.

[0078] One atomic layer deposition cycle includes MoCl5 and high-purity nitrogen: 0.5s, high-purity nitrogen: 20s, H2S and high-purity nitrogen: 0.4s, high-purity nitrogen: 20s. The chamber temperature is 450℃ and the number of cycles is 100.

[0079] S3. Plasma immersion implantation of Ag ions.

[0080] The injection voltage was -10 kV and the plasma density was 1.0 × 10 9 cm -3 , the pulse width is 5μs.

[0081] Comparative Example 2 A method for preparing a surface coating of an air bearing comprises the following steps: S1. Use the anode layer gas ion source to clean the surface of the ball.

[0082] The gas ion source is a mixed gas of Ar and H2, with an Ar flow rate of 100 sccm, a H2 flow rate of 20 sccm, a bias voltage of -150 V, a power of 3 kW, and a time of 60 min.

[0083] S2. Deposit a MoS2 coating in another chamber using atomic layer deposition technology.

[0084] The precursors are MoCl5 and H2S, and MoCl5 is heated to 200°C. The carrier gas is high-purity nitrogen, and the purity of high-purity nitrogen is greater than 99.999%. The flow rate of high-purity nitrogen is 50sccm, and the flow rates of H2S and high-purity nitrogen are 200sccm.

[0085] One atomic layer deposition cycle includes MoCl5 and high-purity nitrogen: 0.5s, high-purity nitrogen: 20s, H2S and high-purity nitrogen: 0.4s, high-purity nitrogen: 20s. The chamber temperature is 450℃ and the number of cycles is 100.

[0086] S3. Plasma immersion implantation of Ag ions.

[0087] In step S4, the injection voltage is -10 kV and the plasma density is 1.0×10 9 cm -3 , the pulse width is 5μs.

[0088] The coatings prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 are compared: (1) The measured bonding strength results are shown in Table 1.

[0089] Table 1 Bonding strength

[0090] (2) When the load is 1N 200rap / min and the time is 60min, the average friction coefficient is shown in Table 2.

[0091] Table 2 Average friction coefficient

[0092] Because the 0.5s MoS2 lubricating layer in Example 2 has the best performance; since the film layer in Comparative Example 1 has poor bonding strength and falls off, the friction coefficient is high.

[0093] (3) When the load is 1N 200rap / min and the time is 60min, the wear rate (10 -5 mm 3 N -1 m -1)The results are shown in Table 3.

[0094] Table 3 Wear rate

[0095] In Example 3, the ZnO layer is thinner, so the wear rate is increased; since the bonding force of Comparative Example 1 is poor and there is shedding, the wear rate is high; Comparative Example 2 has no ZnO, so the wear rate is high.

[0096] (4) The results of the uniformity of the film thickness at different positions of the ball are shown in Table 4.

[0097] Table 4 Uniformity of film thickness at different positions of the ball

[0098] Therefore, the present invention adopts the above-mentioned method for preparing a high-strength and tough lubricating coating on the surface of an air bearing, and removes surface dirt and oxide layer on the surface of the ball through plasma cleaning to improve the bonding strength of the film layer. While further improving the lubrication performance, it can also improve the conductivity of the film layer and prevent the occurrence of discharge.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-strength and tough lubricating coating on the surface of an air bearing, characterized in that: The following steps are involved: S1, using the anode layer gas ion source to clean the surface of the ball; S2, depositing ZnO coating using atomic layer deposition technology; S3, depositing MoS2 coating using atomic layer deposition technology; S4. Plasma immersion implantation of Ag ions.

2. The method for preparing a high-toughness lubricating coating on the surface of an air bearing according to claim 1, characterized in that: In step S1, the gas ion source is a mixed gas of Ar and H2; The Ar flow rate is 50sccm-120sccm, the H2 flow rate is 10sccm-30sccm, the bias voltage is -50V--300V, the power is 1kW-5kW, and the time is 30min-90min.

3. The method for preparing a high-toughness lubricating coating on the surface of an air bearing according to claim 1, characterized in that: In step S2, the precursor is diethyl zinc, the purity of diethyl zinc is greater than 99.99%, and the carrier gas is high-purity nitrogen, the purity of high-purity nitrogen is greater than 99.999%; The flow rate of diethyl zinc is 100 sccm-200 sccm, and the flow rate of high-purity nitrogen is 100 sccm-200 sccm.

4. The method for preparing a high-toughness lubricating coating on the surface of an air bearing according to claim 3, characterized in that: One atomic layer deposition cycle includes, diethyl zinc and high-purity nitrogen: 0.05s-0.15s, high-purity nitrogen: 2s-4s, H2O and high-purity nitrogen: 0.05s-0.15s, high-purity nitrogen: 3s-5s; the chamber temperature is 100℃-350℃, and the number of cycles is 100-500.

5. The method for preparing a high-toughness lubricating coating on the surface of an air bearing according to claim 1, characterized in that: In step S3, the precursors are MoCl5 and H2S, and MoCl5 is heated to 200°C; the carrier gas is high-purity nitrogen, and the purity of the high-purity nitrogen is greater than 99.999%; the flow rate of the high-purity nitrogen is 20sccm-70sccm, and the flow rates of H2S and high-purity nitrogen are 150sccm-250sccm.

6. The method for preparing a high-toughness lubricating coating on the surface of an air bearing according to claim 5, characterized in that: One atomic layer deposition cycle includes: MoCl5 and high-purity nitrogen: 0.5s-1.5s, high-purity nitrogen: 15s-25s, H2S and high-purity nitrogen: 0.3s-0.5s, high-purity nitrogen: 15s-25s; The cavity temperature is 420℃-500℃, and the number of cycles is 75-150.

7. The method for preparing a high-toughness lubricating coating on the surface of an air bearing according to claim 1, characterized in that: In step S4, the injection voltage is -8 kV to 12 kV, and the plasma density is 1.0 × 10 8 cm -3 —1.0×10 10 cm -3 , pulse width is 1.0-15μs.